Cytokine Mixtures Mimicking Secretomes From Mesenchymal Stem Cells Improve Medication‐Related Osteonecrosis of the Jaw in a Rat Model. (6th September 2017) - Ogata, Kenichi; Matsumura, Mayu; Moriyama, Masafumi; Katagiri, Wataru; Hibi, Hideharu; Nakamura, Seiji
ABSTRACT: Recently, several studies have demonstrated that intravenous administration of mesenchymal stem cells (MSCs) improve medication‐related osteonecrosis of the jaw (MRONJ), and paracrine effects of secretomes from MSCs have been hypothesized as the primary contributors. These secretomes in conditioned media from human MSCs (MSC‐CM) were previously demonstrated to promote bone and tissue regeneration. Because MSC‐CM contain cytokines monocyte chemoattractant protein (MCP)‐1, insulin growth factor (IGF)‐1, and vascular endothelial growth factor (VEGF) at relatively higher concentrations than other factors, these cytokines were considered as relevant active factors for tissue regeneration. By mixing the recombinant proteins of MCP‐1, IGF‐1, and VEGF, included at the same concentrations in MSC‐CM, we prepared cytokine mixtures mimicking MSC‐CM and then evaluated its therapeutic effects in a rat MRONJ model. In vitro, cytokine mixtures promoted osteogenic differentiation, migration, and proliferation of rat MSCs. In addition, these maintained osteoclastic function. In vivo, we used a rat MRONJ model to examine therapeutic effects of the cytokine mixtures through intravenous administration. In MSC‐CM or cytokine mixture group, open alveolar sockets in 66% or 67% of the rats with MRONJ, respectively, healed with complete soft tissue coverage and socket bones, whereas in the other groups, the exposed necrotic bone with inflamed soft tissue remained. Histological analysis revealed new bone formation and the appearance of osteoclasts in MSC‐CM or cytokine mixture group; however, osteoclasts were significantly reduced in the other groups. Thus, we concluded that intravenous administration of cytokine mixtures might be an effective therapeutic modality for treating patients with MRONJ. © 2017 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research